Reactions of L-Cyanobromolycopodine - Song, Won-Ryul (My University, 1958)
The reaction of L-cyanobromolycopodine with alkali proceeds with elimination of hydrogen bromide and a new ring is formed in the process, The properties of the compound, L-cyclocyanolycopodine, resulting from this cyclization reaction have been studied and a mechanism for its formation has been postulated. The olefin corresponding to that expected from the elimination of hydrogen bromide from L-cyanobromolycepodine has been prepared indirectly and the oxidative degradation of the olefin has boon investigated.
Keywords: reactions; cyanobromolycopodine